Implementasi Total Quality Management (TQM) Dalam Upaya Meningkatkan Kinerja Karyawan di Cv Idola Indonesia Bandung - Monny Apriana Sismawati; Dewi Yuliati Indah (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This research is motivated by the very tight competitive conditions in the manufacturing industry, where management is required to use a good management system and can be used as a tool to improve employee performance. The purpose of this study was to determine the application of TQM, TQM constraints, and employee performance in CV Idola Indonesia and to determine the effect of TQM implementation in improving employee performance at CV Idola Indonesia. This study uses a descriptive qualitative research approach. This research was conducted at CV Idola Indonesia Bandung. The research informants were the main director, general manager, and employees. The data collection techniques used were observation, interviews, documentation, and literature study. The results of the study can be concluded as follows: (1) The application of TQM in CV Idola Indonesia Bandung consists of five TQM elements which include: focus on customers, obsession with quality, long-term commitment, teamwork, and employee involvement and empowerment. (2) Constraints in the application of TQM at CV Idola Indonesia are differences in attitudes and thoughts between employees. (3) Employee performance at CV Idola Indonesia is seen from the indicators of quality, quantity, timeliness, effectiveness, independence, and work commitment. (4) Employee performance at CV Idola Indonesia increased thanks to the implementation of TQM.